Agreement on Trade and Trade Related Issues between the Republic of the Sudan and the Republic of South Sudan (Tufts Archival Research Center, 2005)
The agreement determines that each State will pursue an independent national trade policy and establishes a Joint Ministerial Committee on Trade Relations.